Plasma Soluble Glycoprotein VI, Platelet Function, Bleeding, and Ischemic Events in Patients Undergoing Elective Percutaneous Coronary Intervention - Lahu, Shqipdona; Adler, Kristin; Mayer, Katharina; Hein-Rothweiler, Ralph; Bernlochner, Isabell; Ndrepepa, Gjin; Schüpke, Stefanie; Holdenrieder, Stefan; Bongiovanni, Dario; Laugwitz, Karl-Ludwig; Schunkert, Heribert; Gawaz, Meinrad; Massberg, Steffen; Kastrati, Adnan; Münch, Götz (Thrombosis and Haemostasis, 2023)
Background and Aims Glycoprotein VI (GPVI) is the major platelet-specific collagen receptor. GPVI shedding with generation of soluble GPVI (sGPVI) is an endogenous feedback mechanism preventing platelet overstimulation. sGPVI has not been investigated in patients with chronic coronary syndrome (CCS) undergoing percutaneous coronary intervention (PCI), especially regarding its potential value as a predictor of ischemic and bleeding risk.Methods Baseline plasma sGPVI levels were available in 318 patients with CCS undergoing PCI. Platelet function was assessed by measuring both adenosine diphosphate (ADP) and collagen-induced platelet aggregation. Co-primary endpoints were a composite of death or myocardial injury at 48 hours after PCI, and Bleeding Academic Research Consortium (BARC) type 1 to 5 bleeding at 30 days.Results There was no significant correlation between sGPVI and platelet function at baseline or at 48 hours after PCI and loading with antiplatelet drugs. Baseline plasma sGPVI levels were not associated with the ischemic risk: the incidence of the ischemic endpoint was 25.0% in the lower, 22.9% in the middle, and 26.7% in the upper sGPVI tertile (p = 0.82). There was a significant nonlinear relationship between sGPVI and the risk of bleeding: the incidence of the bleeding endpoint was 11.8% in the lower, 12.6% in the middle, and 26.4% in the upper sGPVI tertile (p = 0.006).Conclusion In patients with CCS undergoing PCI, plasma levels of sGPVI did not correlate with ADP- or collagen-induced platelet aggregation. Patients with higher baseline levels of sGPVI may carry an increased risk of bleeding at 30 days after PCI but no excess risk of ischemic events.
Keywords: bleeding; chronic coronary syndrome; percutaneous coronary intervention; soluble GPVI; ischemic events